Influência do sistema adesivo na cor de resinas compostas - Ritter, Débora Diniz (2015)
The aim of this study was to evaluate the influence of different adhesive systems in the color of resin composites with different translucency. Sixty specimens of resin composite, in the shades A2 (n=30) e OA2 (n=30) were made with aid of a metallic mould with 8 mm of intern diameter and 1.25 mm of thickness, and randomly divided according to the adhesive system: two-step etch-and-rinse (Adper Single Bond 2; 3M ESPE), two-step self-etch (Clearfil SE Bond; KURARAY) and universal (Single Bond Universal; 3M ESPE). The materials were applied on the surface of the disk-shaped specimens, simulating direct restorations. The color evaluations were measured with spectrophotometer immediately after the polishing the specimens and after the application of the adhesive systems. The data of CIE L*a*b* system were used for the calculus of ΔE, ΔL, Δa e Δb. Additionally, 5 specimens of each adhesive system were made with the same dimensions of the disks of resin composite for measurement of the L*, a* e b* parameters. The data obtained were subjected to Analysis of Variance and Tukey test (5%). The application of the adhesive system Single Bond Universal on resin composite A2 resulted in highest color change p= 0.000; ΔE = 3.1 ± 0.7). No statistical significant difference was observed among adhesive systems when applied on resin composite shade OA2 (p>0.05). The universal adhesive showed higher trend to green and yellow. In conclusion, the effect of the adhesive system is material-dependent. The adhesive Single Bond Universal results in higher color change when a resin composite with higher translucency is used.